Prevalência de demência entre os idosos do município de Aracaju/SE - Silva, Roberto Cotias (2019)
Introduction: The world is undergoing a process of change in the demographic pyramid. demographic pyramid. The elderly population is growing in relative and absolute numbers. This fact is associated with increased morbidity and mortality from chronic diseases. Dementia, which is characterized by varying degrees of cognitive decline, has doubled in prevalence every five years in people over 65. The objective of this article is to estimate prevalence of cognitive decline in the elderly population of the municipality of Aracaju-SE. Methods: This will be a cross-sectional study. The reference population of the study were individuals from 60 years of age, of both sexes and not institutionalized and developed with residents in the urban area of the city. The collection was carried out in the period from May 2017 to June 2018, using a structured interview script with open and closed questions. open and closed questions. For the investigation, it was considered as an outcome the cognitive decline investigated from the use of the MMSE. Results: Of the 66 elderly interviewed, 62.12% were female and the mean age was 73.8 years (±9.19). The functional capacity indicators were evaluated based on their performance in the IADL and ADL. Dependence in IADL was reported by 57.58% of the elderly, while dependence in ADL was reported by 12.13%. About the test performed with the MMSE instrument, it was noticed that 26 elderly had scores below 23 points, corresponding to a prevalence of 39.39% of cognitive decline in this sample. Discussion: The prevalence of cognitive decline in the population of Aracaju was higher than in more developed cities of the country and the world. We also found a higher association of dementias with the female gender and those older than 80 years. We found significant functional disability in the elderly, compromising their quality of life and that of their caregivers